Tomando buenas decisiones: Medios de comunicación y salud física de los niños pequeños, consejos para los padres - David C. Diehl; Stephanie C. Toelle (EDIS, 2011)
Now available in Spanish, this is part of a series of publications by David C. Diehl and Stephanie C. Toelle that addresses media and its effects on young children, from birth to age six. The series is designed to reach both professional educators and parents and to provide research summaries, tips for parents, and internet resources for further information. Spanish versions published by the UF Department of Family Youth and Community Sciences, June 2011. UF/IFAS photo: Thomas Wright.